The Soviet-Japanese War of 1945 on the pages of textbooks of basic secondary education - A. P. Artyukov; A. E. Amelin (Вестник Самарского университета: История, педагогика, филология, 2023)
The article deals with the problem of studying the Soviet-Japanese War in the system of basic general education, through a comprehensive analysis of information material in school textbooks from 1952 to the present. The relevance of this topic is explained by certain specifics of Russian-Japanese relations, which can be described as restrained, due to a number of territorial, economic and political contradictions. Almost every year, Japan raises the issue of the territorial affiliation of some islands of the Kuril ridge, putting forward claims and calls for a revision of decisions taken following the Second World War. But Japanese diplomacy faces a firm position of the Russian Federation on this issue. Such diplomatic battles have been going on since the middle of the last century to this day and are the reason that a peace treaty between the countries has not been concluded yet. In modern conditions of aggravation of international relations, the topic of the Soviet-Japanese war of 1945 and the results of the Second World War in the education system are becoming one of the key topics. In the study of educational materials of textbooks on the topic of the Soviet-Japanese war, the main attention was paid to the volume of historical material presented to students for study, illustrative material, the content part, that is, how much the topic is disclosed as fully and in detail as possible, as well as schematic maps. Thus, the analysis of the content of the text material in textbooks revealed the wave-like dynamics of the information volume, from the quantitative and qualitative growth of historical information, especially in the early 1980s, to its sharp reduction in the materials of modern textbooks.